Wine tourism and wine marketing in family-owned micro wineries in Guadalupe Valley, Mexico - García Fernández, Adrián; Meraz-Ruiz, Lino; Díaz Gómez, Eduardo Raúl (My University, 2018)
Given the importance of the wine sector in Baja California, Mexico, the purpose of this research is to explore the tourism and marketing characteristics of family-owned micro wineries with a production of no more than 5,000 annual/boxes of wine from the Guadalupe Valley, and to identify the socio-demographic consumption parameters. Based on the results, recommendations were made with the cautionary note that more research is needed to address the gap of information that exists in this topic. The research design was a mixed one, qualitative and quantitative, in which a convenience sample of 200 visitors to the Guadalupe Valley were surveyed, and 17 experts in the domain area were interviewed, which allowed to gather data about wine shopping behavior, wine marketing, wine tourism and country background. The results indicated the existence of a significant relationship between dependent and independent variables using Chi Square analysis in SPSS (type of wine + frequency of consumption, type of retailer and willingness to pay). Additionally, a large number of smaller, family-owned wineries, that have limited production runs, and diversify their services via restaurant and boutique type lodging, was uncovered. Conclusions are drawn and implications discussed.
Rosa dos ventos turismo e hospitalidades
Keywords: Wine tourism; Marketing; Small family wineries; Baja California (State)